Music to My Ears:The Terms ‘nona’ and ‘nyonya’ as Ethnonyms and Beyond - Tan, Raan Hann; Silvio, Moreira de Sousa (Pusat Pengajian Ilmu Kemanusiaan, 2019)
According to dictionaries of Standard Malay, nyonya means the married woman of a Chinese or a European, whereas nona stands for an un-married, young woman of European or Chinese descent. Hence, a dichotomous relation is reflected in the meanings for these two terms. Nowadays, nyonya almost refers exclusively to a Chinese Peranakan lady. This is the connotation of the term in Baba Malay and it is clearly visible in the ethnonym baba-nyonya or in designations of cultural areas connected to the Chinese Peranakan such as ‘baba-nyonya language’, ‘nyonya food’, ‘nyonya kuih’, or ‘nyonya clothing’. These labels coexist with other labels like ‘peranakan cuisine’ and ‘peranakan fashion’. As for nona, the word also has a different significance in the Portuguese creole varieties of Melaka (Malaysia) and Tugu (Indonesia). Parents in Portuguese Eurasians families address their daughters by the term nona, but, unlike nyonya for the Chinese Peranakans, nona is not an ethnonym for the female members of the Portuguese Eurasian communities in Indonesia, Malaysia, and Singapore. Sarkissian (1995) and Jackson (2007) analyzed the song Jinkli Nona and demonstrated that the beautiful and exotic “Portuguese” damsel - in fact, a Eurasian-African-Sinhalese “nona” - had “become synonymous over time with South and Southeast Asian women in areas influenced by Indo-Portuguese maritime contacts, both etymologically and aesthetically” (Jackson 2007: 213). In the context of Malaysia, the song is now considered a national song that is known by all ethnic groups, young and old. Expanding from there, the objective of this paper is to observe how music has influenced the meaning of the terms nyonya and nona, and to understand how the terms nyonya and nona shifted semantically between languages and nations, if that is the case. Further analysis could take into perspective pantuns and poems.